A Study on the Biodiversity of Aquatic Invertebrate Fauna of Nizamsagr Irrigation Reservoir, Kamareddy District, Telangana, India - Reddy , G. Srinivas; Balakrishna , D.; Reddy , T. Ravinder (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Nizamsagar reservoir constructed across the river Manjeera between Achampeta and Banjapalli villages of newly formed Kamareddy district of Telangana State. The River Manjeera is a tributary river of the Godavari. The height of the dam is 96 meters and length is 3 km having water capacity 30 TMC. The study revealed that a total of 27 invertebrate species belonging to three phyla: Arthropoda, Mollusca, and Annelida. Among these, the Arthropoda phylum species dominated, followed by Mollusca and Annelida. In the Mollusca phylum, the Gastropoda class exhibited rich abundance, with species like Bithynia transsilvanica, Bellamya bengalensis, Perrysisfavidens, and Pila globose being prominent. Within the Annelida phylum, Tubifex tubifex in the Clitellata class showed the highest abundance compared to Limnodrillus hoffmeisteri. In the Arthropoda phylum, specifically in the Insecta class, there were a diverse range of species, including Chironomus Sps., Anophelus mosquito larvae, Culex mosquito larvae, Sympetrum vulgatum, and Orthetrum cancellatum, with the highest diversity observed.